Genome‐wide association study identified genes in the response to Salmonella pullorum infection in chickens. (24th April 2019) - Xiao, L.; He, C.; Luo, L.; Yang, K.; Yang, L.; Xu, K.; Zheng, Y.; Gu, C.; Huang, Q.; Meng, H.
Summary: Pullorum is a bacterial disease that threatens the modern poultry industry. Over the years, research on this topic has focused mainly on its epidemiology, whereas the hosts' genetic basis of infection is still vague. In order to identify chickens' genes associated with pullorum, we sequenced 300 New Pudong chicken by double digest genotyping‐by‐sequencing. We obtained 1 527 953 SNPs for a genome‐wide association analysis, which identified 43 genome‐wide significant markers. Most of the significant SNPs were in the interval of 57.7–59.0 Mb on chromosome 5. The gene set enrichment analysis suggests a potential manner for bacterial infection and remaining inside the host. This work provides basic data for the purification, prevention and treatment of pullorum disease.